Empowered women prioritize the environmental and health impacts of fuel choice: Empirical evidence from Central Asia - Dina Azhgaliyeva; Hans Holzhacker; Dil Bahadur Rahut; James Correia (Asian Development Bank Institute (ADBI), 2024)
Women face substantial and specific challenges from the use of solid fuels. The persistence and prevalence of traditional gender roles in many societies mean that women and girls are often responsible for gathering and managing solid fuel supplies. Significant time and effort is required for collecting solid fuels, and using them for domestic purposes increases exposure to the health risks of household air pollution and could limit educational and employment opportunities. As a result, strategies to address energy poverty and advance the green transition need to pay particular attention to women's empowerment, including improving their access to energy, reducing their dependence on polluting fuels, and ensuring their representation in energy decision-making processes. To investigate the energy choices of the energy-poor population, we conducted a survey of 1,522 households from the Fergana Valley in three Central Asian countries: eastern Uzbekistan, the southern Kyrgyz Republic, and northern Tajikistan. The majority of household heads explicitly acknowledge that fossil fuels are harmful for the environment and/or the health of their families. Nevertheless, most prioritize financial costs, the reliability of their energy supply, or their existing heating system in their fuel choice. The empirical evidence shows that employed females are more likely than employed males to prioritize the environmental and health impacts of fossil fuels. This provides evidence of the importance of female empowerment through employment for promoting energy transition.
Keywords: G50; G51; G53; 330; gender; female; Central Asia; heating; fossil fuel; air pollution